2005
DOI: 10.1177/153537020523000305
|View full text |Cite
|
Sign up to set email alerts
|

Soybean-Derived Phytoestrogens Regulate Prostaglandin Secretion in Endometrium During Cattle Estrous Cycle and Early Pregnancy

Abstract: Phytoestrogens acting as endocrine disruptors may induce various pathologies in the female reproductive tract. The purpose of this study was to determine whether phytoestrogens present in the soybean and/or their metabolites are detectable in the plasma of cows fed a diet rich in soy and whether these phytoestrogens influence reproductive efficiency and prostaglandin (PG) synthesis during the estrous cycle and early pregnancy in the bovine endometrium. In in vivo Experiment 1, we found significant levels of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
81
5
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 59 publications
11
81
5
2
Order By: Relevance
“…The concentrations of P4, PGFM and PGE2 in the plasma and medium samples were determined with direct enzyme immunoassays (EIAs), as described previously [28]. The anti-P4 serum was donated by Prof S Okrasa, University of Warmia and Mazury in Olsztyn.…”
Section: Hormone Determinationmentioning
confidence: 99%
“…The concentrations of P4, PGFM and PGE2 in the plasma and medium samples were determined with direct enzyme immunoassays (EIAs), as described previously [28]. The anti-P4 serum was donated by Prof S Okrasa, University of Warmia and Mazury in Olsztyn.…”
Section: Hormone Determinationmentioning
confidence: 99%
“…Before and during the mating period the C and P diets included 20% of grass meal and 20% of alfalfa meal, respectively. The levels of phytoestrogens in the diets were determined by HPLC (Woclawek-Potocka et al, 2005). Con-centrations of total phytoestrogens in the C and P diets were 210.38 and 383.55 µg/g during the growth period and 15.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Moreover, Lundh et al [11] showed in cows that the daidzein and genistein present in fodder are immediately converted in the rumen to equol and para-ethyl-phenol, respectively. We showed in our previous study that there are significant levels of daidzein, genistein and their metabolites in the soy beans fed to dairy cattle [6]. High concentrations of isoflavone metabolites (equol and para-ethyl-phenol) are present in the blood of cows fed soy bean [6,9].…”
mentioning
confidence: 93%